2014
DOI: 10.4236/msce.2014.25004
|View full text |Cite
|
Sign up to set email alerts
|

Calcined Clay Pozzolan as an Admixture to Mitigate the Alkali-Silica Reaction in Concrete

Abstract: Calcined clay pozzolan has been used to replace varying portions of high alkali Portland limestone cement in order to study its effect on the alkali-silica reaction (ASR). Portland limestone cement used for the study had a total Na2Oeq of 4.32. Mortar-bar expansion decreased as pozzolan content in the cement increased. The highest expansion was recorded for reference bars with no pozzolan, reaching a maximum of 0.35% at 42 days whilst the expansion was reduced by between 42.5% and 107.8% at 14 days and between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 13 publications
2
19
0
Order By: Relevance
“…This is in line with the findings of other studies [32,36], that CH is the most allergic component for the corrosive media. CH is consumed during pozzolanic reaction, thus reducing CH content durability of hydrated cement is improved [32][33][34][35][36]. It was also found that the "Calcined" clay modified samples showed more resistance to sulfate attack than that of "As is" clay modified samples as shown.…”
Section: "800°c Calcined" Mmt Modified Mortarssupporting
confidence: 93%
See 3 more Smart Citations
“…This is in line with the findings of other studies [32,36], that CH is the most allergic component for the corrosive media. CH is consumed during pozzolanic reaction, thus reducing CH content durability of hydrated cement is improved [32][33][34][35][36]. It was also found that the "Calcined" clay modified samples showed more resistance to sulfate attack than that of "As is" clay modified samples as shown.…”
Section: "800°c Calcined" Mmt Modified Mortarssupporting
confidence: 93%
“…Excess Mmt above this 25% replacement level is more than the pore filling requirement that causes weakness, which can lead to an increase in sulfate attack, ultimately reducing the compressive strength [50]. This is in line with the findings of other studies [32,36], that CH is the most allergic component for the corrosive media. CH is consumed during pozzolanic reaction, thus reducing CH content durability of hydrated cement is improved [32][33][34][35][36].…”
Section: "800°c Calcined" Mmt Modified Mortarssupporting
confidence: 88%
See 2 more Smart Citations
“…The low porosity in blended cement mortars can be attributed to the fact that pozzolana materials such as calcined clays increase nucleation sites for precipitation of hydration products resulting in pore refinement thus lowering the porosity [26]. CH produced during hydration of OPC-H 2 O consumed in pozzolanic reaction forming secondary CSH and CAH [27].…”
Section: Porositymentioning
confidence: 99%